2004
DOI: 10.1207/s15328023top3103_5
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Forum

Abstract: We investigated students' perceptions of the distinction between ideal and typical teachers using a 40-item survey that solicited responses to professors' personal characteristics, course design and policies, and classroom behavior. Compared to their Typical professor, students' Ideal professor was, in some ways, more lenient, but also more accessible, personable, open to variation, and clear about course policies. We suggest that Ideal teachers capitalize on a subset of behaviors that strengthen the investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition to their broad pedagogical approach, model teachers also possess mastery of many specific teaching skills. There is some consensus on the skills and classroom stance of the best college teachers Epting, Zinn, Buskist, & Buskist, 2004;Keeley et al, 2006Keeley et al, , 2010Marsh, 1984;Svinivki & McKeachie, 2011 (Cerbin, 2012). Lesson plans, at a minimum, contain a list of learning objectives and the materials and methods the teacher will use to facilitate learning.…”
Section: Model Teachers Are Well Versed In Instructional Methodsmentioning
confidence: 99%
“…In addition to their broad pedagogical approach, model teachers also possess mastery of many specific teaching skills. There is some consensus on the skills and classroom stance of the best college teachers Epting, Zinn, Buskist, & Buskist, 2004;Keeley et al, 2006Keeley et al, , 2010Marsh, 1984;Svinivki & McKeachie, 2011 (Cerbin, 2012). Lesson plans, at a minimum, contain a list of learning objectives and the materials and methods the teacher will use to facilitate learning.…”
Section: Model Teachers Are Well Versed In Instructional Methodsmentioning
confidence: 99%
“…Profiles described by younger students, and by students matriculating straight from high school, appear to have a repeated pattern in literature (Epting et al;Feldman, 1988;Carlan, 2001). In the studies mentioned above, age played a significant role, since older students described their ideal professor as organized and flexible, while they also presented the ideal class as an organized one.…”
Section: Evaluation Of the Ideal Professormentioning
confidence: 88%
“…In the study of Epting et al (2004), certain characteristics appear both in the typical and the ideal professor, such as the clear speech (93 % for the ideal and 80% for the typical) and the daily appearance of the course's goals in the syllabus (83% and 52%). The above characteristics are, however, part of the "technical" educational procedure.…”
Section: Portrait Of the Ideal Professormentioning
confidence: 99%
See 1 more Smart Citation
“…Instructors who are perceived as more available to students are considered ideal instructors (Epting, Zinn, Buskist, & Buskist, 2004). Sander, Stevenson, King, and Coates (2000) found that among college students, availability was the second most desirable behavior in instructors.…”
Section: Literature Reviewmentioning
confidence: 99%